Analisis Proksimate Campuran Batubara Dengan Arang Tempurung Kelapa Terhadap Nilai Parameter Kualitas Batubara - mustaqim nashra; fadhilah fadhilah (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Atoz Nusantara Mining is a company engaged in coal mining, currently coal mining activities are less effective because companies that do so do not utilize low quality coal. Low quality coal accumulates in the stockpile and is not sold because of low quality coal, refining or processing the coal so that it can be utilized. The comparison of coal mixture with coconut shell charcoal is 10gr coal: 2.5gr charcoal, 10gr coal: 5gr charcoal, 10gr coal: 7.5g charcoal, 10gr coal: 10gr charcoal. The research method was carried out by testing the nearest calorific value, sulfur and coal. Based on the results of the research, the effective ratio of coal calorific value is 10gr coal: 10gr charcoal. The initial calorie of coal is 5100 cal / g after mixing, the calorie value of coal is 6061 cal / gr, then the initial sulfur test coal is 1.37% to 0.57%. , 26%, then in the initial test the volatile matter was 8.79% to 17.08%, the initial coal ash value test was 15.57% to 10.7%, and the initial coal calculation of the fixed carbon value was 69.57%. 65.94%. From the results of the study it can be concluded that mixing coal with coconut shell charcoal is very effective in improving the quality of coal, especially in increasing the heating value and volatile matter and is effective in reducing sulfur levels.Keywords: Quality of coal, charcoal, calories, ash, volatile matter